2008
DOI: 10.1097/chi.0b013e31816765ab
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Mapping of Hippocampal Anatomy in Adolescents With Bipolar Disorder

Abstract: Objective-Early-onset bipolar disorder is thought to be a particularly severe variant of the illness. Continuity with the adult form of illness remains unresolved, but preliminary evidence suggests similar biological underpinnings. Recently, we observed localized hippocampal decreases in unmedicated adults with bipolar disorder that were not detectable with conventional volumetric measures. Using the same three-dimensional mapping methods, we sought to investigate whether a similar pattern exists in adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 63 publications
3
46
1
1
Order By: Relevance
“…Decreased HCV may be more prominent in cases of pediatric as opposed to adult BP [9,11,15,32,33]. On the other hand, some studies found no structural differences for HCVs in youths with BP, similar to our results [12,13,14].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Decreased HCV may be more prominent in cases of pediatric as opposed to adult BP [9,11,15,32,33]. On the other hand, some studies found no structural differences for HCVs in youths with BP, similar to our results [12,13,14].…”
Section: Discussionsupporting
confidence: 81%
“…In fact, the HC may be one of the earliest structures to be negatively impacted by the disorder [34]. A recent study using three-dimensional modeling found significant volume reductions in HCV among youths with BP and alterations in the volumetric changes associated with age [15]. Nevertheless, the findings of cross-sectional structural MRI studies in children and youths have been controversial.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…33 However, these findings were consistent with previous studies using surface-based method. 29 It is worth mentioning that our study was able to consider for two important variables in the study of hippocampus changes in patients with BD, such as the lithium effect on the hippocampus (Supplementary Materials) and the effect of BD types. Indeed, several important studies, including meta-analyses reported the neuroprotective effect of lithium in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have made great advancement in understanding the morphometric and volumetric changes in the hippocampus in mood disorders using surface-based shape analyses 14,28,29 or an automated method of labeling the subfields based on an in vivo atlas. 30,31 However, the surface-based shape analysis could not reach deep structures of the hippocampus.…”
Section: Introductionmentioning
confidence: 99%